Prolotherapy with 12.5% dextrose to treat temporomandibular joint dysfunction (TMD) - Ehab Shehata (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2019)
Introduction: Temporomandibular joint dysfunction (TMD) is a collective term used to describe a complex and multifactorial disorders of the orofacial region. Symptoms commonly associated with TMD include TMJ pain, limited mandibular movement or locking and painful clicking or popping sounds. Most of patients diagnosed with TMD are initially treated conservatively. Failure of such conservatism poses a great challenge for the treating physician. Prolotherapy has been used successfully in many joints in the body by orthopedics and spinal surgeons. Injection prolotherapy has also been used in management of weakening tendons or ligaments in head and neck. Aim of the study: To evaluate the efficacy of dextrose prolotherapy with 12.5% concentration in the treatment of intractable temporomandibular joint dysfunction. Material & Methods: A prospective clinical study with 33 patients with the diagnosis of TMD were included in this study during the period from Jan. 2012 to Jan.2015. Inclusion criteria were; adult patients above 18 years old, with TMD symptoms for more than 6 months, had failed conservative treatment and have no pathological findings on dynamic magnetic resonance imaging. Prolotherapy was achieved by six sessions of 12.5% dextrose (3ml) injection per joint with one month interval. A Semi-structured questionnaire developed by the author was utilized to gather all demographic data. All variables were collected, tabulated and analyzed. Follow up appointments were booked after the last session, every 3 months for up to 24 month. Results: I used maximum mouth opening, clicking and visual analogue pain score to judge the efficacy of my protocol. There was statistical significant improvement of all previous variables outcomes.  Conclusion: Dextrose prolotherapy can be used in patients diagnosed with TMD whom had failure of conservative treatment to control their symptoms. More than four prolotherapy sessions is not recommended as per results of this study. It is safe and efficient technique.